Manajemen integrasi al-Qur’an dalam pembelajaran ‎matematika di MA al-Ma’arif Singosari: Langkah awal ‎menuju pembelajaran terintegrasi al-Qur’an - khoirunnisak, khoirunnisak (Maliki Interdisciplinary Journal, 2023)
Mathematics learning at MA Al-Ma’arif Singosari is still not integrated with the Al-Qur’an Hadits. This can be seen from the results of observations made in a structured participant manner and structured interviews with reference to the observation guidelines and interview guidelines that have been made. From the learning tools MA Al-Ma’arif Singosari has not integrated and only provides general perceptions related to everyday life without linking it to the Al-Qur’an Hadits. Teacher readiness in integrated mathematics learning still requires quite a lot of preparations, both related to media in the form of modules or teaching materials. Meanwhile, their students feel interested if learning mathematics is integrated with the Al-Qur’an Hadits. So that to carry out integrated mathematics learning of the Qur’an Hadits it is necessary to consider the readiness of both the teacher, students and other elements involved.